Demand risk management of private High-Speed Rail operators: A review of experiences in Japan and Taiwan. (November 2021) - Bugalia, Nikhil; Maemura, Yu; Ozawa, Kazumasa
Abstract: Demand risks are critical for the involvement of private sector participants in High-Speed Rail (HSR) operations. This study examines specific cases of the organizational characteristics of HSR operators that have successfully managed demand risks. By examining the successful operational performance of vertically integrated private HSR operators in Japan and Taiwan, and the influence of government regulations in enabling such successes, the study aims to provide a discussion on the appropriate balance between the risk and control sharing by public authorities and private HSR operators. In our analysis, continuous improvement in the quality of services is identified as a rational strategy for sustaining passenger business. Crucial factors have been identified by examining the application of a continuous improvement strategy in a delay-management system utilized by one of the private HSR operators in Japan. Our study highlights the importance of actions such as integrated operations and maintenance management towards continuous service improvement. Moreover, the effectiveness of these actions is identified to be enabled by management factors such as financial management. The discussion reveals how government regulations can influence the corporate governance of a private HSR operator and potentially restrict the efficiency of service improvement strategies. The importance of institutional factors reemphasizes the need to learn from the experiences of existing HSR projects and to find applications for developing countries expecting a similar HSR operating environment. The findings suggest that the independent corporate-governance for private HSR operators should be considered thoroughly by public actors that contemplate any risk-sharing arrangement with the private sector. Highlights: Consideration for functional-bundling is essential for risk-sharing in railway PPPs. Technical innovation and human capacity are the pillars of service quality. Intra-organizational coordination supports continuous service quality improvement. Government regulation affects the private operator's effort for service improvement. While sharing risks railway operators' corporate governance should be independent.